Symbols of resistance : a tribute to the martyrs of the Chican@ movement - Montaño, Brenda (The Freedom Archives, 2017)
"Symbols of Resistance illuminates the untold stories of the Chican@ Movement with a focus on events in Colorado and New Mexico. The film engages student activists, the effect of police repression, and how issues of identity, land, and community still resonate in the Chican@ struggles of today. Through interviews with those who shaped the movement and rare historical footage, Symbols of Resistances offers a window into a dynamic moment in history and movement building."--Publisher's website.